The right ventricle in Fabry disease: natural history and impact of enzyme replacement therapy. Issue 23 (21st October 2010) - Niemann, Markus; Breunig, Frank; Beer, Meinrad; Herrmann, Sebastian; Strotmann, Jörg; Hu, Kai; Emmert, Andrea; Voelker, Wolfram; Ertl, Georg; Wanner, Christoph; Weidemann, Frank
Abstract : Background: Storage of globotriaosylceramides is present in the left and right ventricles of patients with Fabry disease. Improvement of left ventricular morphology and function during enzyme replacement therapy (ERT) has previously been reported. Objectives: To analyse the effects of long term ERT on right ventricular morphology and function. Methods: This was a prospective follow-up of 75 genetically confirmed consecutive Fabry patients for 3.1±1.8 years. According to treatment guidelines the natural history was followed in 18 patients, whereas 57 patients received ERT. Standard echocardiography, strain rate imaging for regional deformation of the right and left ventricle, and magnetic resonance tomography with late enhancement (LE) imaging for the detection of fibrosis were all performed at yearly intervals. Results: Right ventricular hypertrophy was evident in 53 patients (71%) at baseline. A significant positive correlation was found between left and right ventricular wall thickness (r=0.76; p<0.0001). LE was detected in half of the patients (n=38) in the left ventricle at baseline while no patient ever had LE of the right ventricle. Patients with LE in the left ventricle presented with the lowest right ventricular deformation properties. In contrast to the left ventricle, there was no change in right ventricular wall thickness (baseline 6.9±1.6 mm vs follow-up 6.7±1.5 mm; p=0.44) or systolic strain rate (2.2±0.7/s vs 2.1±0.8/s; p=0.31) during follow-up with ERT. Conclusion: The degree of right ventricular involvement in Fabry disease is related to the left ventricular cardiomyopathy stage. ERT seems to have no direct impact on right ventricular morphology and function.